2011
DOI: 10.1002/app.33986
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of polytetrafluoroethylene/CaCO3 hybrid hollow fiber membranes

Abstract: A novel method of preparing polytetrafluoroethylene (PTFE) hollow fiber membrane was presented by utilizing poly (vinyl alcohol) (PVA) can form a gel of two dimensional complex compounds with Boric acid (H 3 BO 3 ). Effects of H 3 BO 3 on PTFE nascent hollow fiber were investigated, and the results showed that the introduction of H 3 BO 3 effectively reduced the addition of PVA. The configuration named ''fibril'' formed between PVA and H 3 BO 3 could be observed in nascent hollow fiber by SEM (Scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…According to FTIR analysis, the vibration of hydroxyl groups weakened while BA mingled in PVA or on DND, and the peaks for BOC or COC bonding were strengthened. These results show that the hydroxyl species of the components bonded and dehydration occurred amid the crosslinking process, resulting in the construction of oxo‐bridges …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…According to FTIR analysis, the vibration of hydroxyl groups weakened while BA mingled in PVA or on DND, and the peaks for BOC or COC bonding were strengthened. These results show that the hydroxyl species of the components bonded and dehydration occurred amid the crosslinking process, resulting in the construction of oxo‐bridges …”
Section: Resultsmentioning
confidence: 84%
“…These results show that the hydroxyl species of the components bonded and dehydration occurred amid the crosslinking process, resulting in the construction of oxobridges. 8,33,34 Application Properties of Composite Films Mechanical Properties of PVA Films. Table I shows the data of tensile strength (r max ), elongation at break (E max ), and Young's modulus (E) for pure PVA film and composite films of PVA/ BA, PVA/DND, and PVA/BA/DND, and curves illustrating r-E relationship and the influence of the BA-modified DND content on the E value of the films are shown in Supporting Information S3.…”
Section: Article Wileyonlinelibrarycom/appmentioning
confidence: 99%
“…The maximum pore size ( D max ) was measured using the gas bubbling method and calculated by the following Eq. 5 25: …”
Section: Methodsmentioning
confidence: 99%
“…As is well‐known, each step of the paste extrusion process is critical in determining the final membrane properties. Furthermore, stretching is supposed to be the key step for porous structure formation 22–25. Kitamura et al studied the formation mechanism of porous structures in PTFE membranes by microscopy 26.…”
Section: Introductionmentioning
confidence: 99%
“…Kawai in Japan provided the method and porous PTFE hollow fiber membrane with pores of 0.3–2.0 µm, porosity of about 40%. Huang in China did much works on PTFE hollow fiber membrane (porosity 38.6%, water contact angle 134.68°) to reduce the addition of fiber‐forming polymer and obtain the porous microstructure of interfacial microvoid. As a result of above studies about emulsion spinning, it is found that the membrane product suffers from inferior porosity and permeability performance.…”
Section: Introductionmentioning
confidence: 99%